Battery‐Free and Wireless Technologies for Cardiovascular Implantable Medical Devices. Issue 6 (7th January 2022) - Zhang, Jungang; Das, Rupam; Zhao, Jinwei; Mirzai, Nosrat; Mercer, John; Heidari, Hadi
Abstract: Cardiovascular disease continues to be one of the dominant causes of global mortality. One effective treatment is to utilize cardiovascular implantable devices (cIMDs) with multi‐functional cell sensing and monitoring features that have the potential to manipulate cardiovascular hyperplasia disorders as well as provide therapy. However, batteries with a fixed capacity entail high‐risk surgeries for battery‐replacement, which causes health hazards and imposes significant costs to patients. This review accesses comprehensive power solutions for cIMDs, from conventional batteries to state‐of‐the‐art energy harvesters and wireless power transfer (WPT) schemes. In particular, WPT has great potential to eliminate the percutaneous wires and overcome frequent battery removal. Here, the fundamentals, power transfer efficiency, antenna design and miniaturization, and operating frequencies in various WPT schemes are presented. Moreover, the power loss attenuation and bio‐safety standard (specific absorption rate) for implants are also considered in WPT design envelope. In addition, wireless data transmission of implantable devices from external to internal milieu (and vice versa) along with different modulation and demodulation techniques are investigated. The last advanced power solutions for cIMDs in in‐vivo and in vitro research are illustrated throughout. Finally, specifications and future potential of WPT systems in cIMDs are highlighted. Abstract : This study approaches various power solutions for cardiovascular implants, from conventional batteries to state‐of‐the‐art energy harvesters and wireless power transfer (WPT) schemes. The advanced power solutions for cardiovascular implants in in vivo and in vitro experiments are illustrated throughout. Finally, specifications and future potential of cardiovascular WPT system are highlighted, and their performance is compared with that of other state‐of‐the‐art devices.